Fatty acid synthase: A key driver of ovarian cancer metastasis and a promising therapeutic target - Nuha Ahmad (22302754) (2024)
Fatty acid synthase (FASN) is a critical enzyme essential for the production of fats in the body. The abnormal expression of FASN is associated with different types of malignancies, including ovarian cancer. FASN plays a crucial role in cell growth and survival as a metabolic oncogene, although the specific processes that cause its dysregulation are still unknown. FASN interacts with signaling pathways linked to the progression of cancer. Pharmacologically inhibiting or inactivating the FASN gene has shown potential in causing the death of cancer cells, offering a possible treatment approach. This review examines the function of FASN in ovarian cancer, namely its level of expression, influence on the advancement of the disease, and its potential as a target for therapeutic interventions. Other Information Published in: Pathology - Research and Practice License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.prp.2024.155465